IMPLEMENTATION OF MIDWIFERY CARE DOCUMENTATION FOLLOWING THE MINISTRY OF HEALTH OF REPUBLIC INDONESIA DECREE NO HK.01.07/MENKES/320/2020 - Evi Zulfiana; Akhmad Aniq Barlian (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Professional services and legal aspects of the midwifery profession are some of the duties of the midwife. However, in making midwifery care documentation, many midwives were not following the regulations, while this is one of the midwives' violations. This study aimed to determine how the implementation of midwifery care documentation following the Minister of Health Decree on professional standards midwife. The method used in this study was qualitative—data collection using human instruments and interview guidelines. The sample of this research was four private practice midwives as primary informants and the head of the Indonesian Midwives Association as a triangulation informant. The results showed that the documentation management carried out by the four informants was not following the Ministry of Health's decree because midwives still using narrative techniques, namely recording examination results without writing down progress notes. The obstacle encountered was that documenting midwifery care took a long time; there have been no complaints from the community regarding unsystematic documentation methods. There were no sanctions to the midwives who did not document their services as correct. This finding is inconsistent with the Minister of Health concerning licensing and implementation of midwifery practices article 46.Keywords: Documentation of Midwifery Care, Midwife Professional Standard